Deconstruction of identity concepts in Islamic State propaganda: a linkage-based approach to counter-terrorism strategic communications : this paper was presented at the 1st European Counter Terrorism Centre (ECTC) Conference on Online Terrorist Propaganda, 10-11 April 2017, at Europol Headquarters, The Hague (Europol, 2017)
The research conducted by the ECTC Advisory Group on Online Terrorist Propaganda between October 2016 and April 2017 was presented in the 1st ECTC Conference on Online Terrorist Propaganda (10-11 April 2017) and resulted in the following publication.